Co-morbidities to Vestibular Impairments—Some Concomitant Disorders in Young and Older Adults - Malmström, Eva-Maj; Ekvall Hansson, Eva; Hafström, Anna; Magnusson, Måns; Fransson, Per-Anders (Frontiers in Neurology, 2021)
Background: Dizziness and pain are common complaints that often appear concomitantly, with or without a causal relationship. However, these symptoms might maintain and exacerbate each other and other co-morbidities. Therefore, adequate rehabilitation may have to include an expanded focus on other deficits and preconditions, especially in older adults and in patients. Objective: To understand how frequently vestibular dysfunction coincided with medical conditions and aging, we studied two categories: Study 1: patients referred to a vestibular unit and Study 2: senior members in a fitness association. Method: Study 1: Forty-nine patients (34 females/15 males; mean age 52 years (SEM 2.0)) seeking health care for balance disorders and vestibular deficits were asked in questionnaires about their perception of dizziness and pain, and emotional and functional strains. Study 2: One-hundred-one senior members in a fitness association (91 females/10 males; mean age 75 years (SEM 0.6)), were assessed for vestibular and balance deficits and for any co-morbidities. The participants were monitored for falls for 12 months after the initial assessments. Result: Study 1: Co-morbidity often existed between dizziness and pain (65 %). The patients also reported high emotional and functional strain related to their dizziness and pain. Patients older than 60 years reported longer durations of pain (p≤0.028) but less emotional strain (p=0.036), compared to younger patients. Study 2: Eighty-four percent of the participants had a vestibular impairment, often without noticing any symptoms. Furthermore, 40% reported cardiovascular illnesses, 12% musculoskeletal disorders, and 63% reported other medical conditions. Forty-two percent experienced falls within one year after the initial assessments (thereof 42% in the group with vestibular deficits and 38% in the group without vestibular deficits). Conclusion: To enhance and preserve postural control, both in patients with vestibular deficits and in older adults, we suggest an expanded clinical perspective. Hence, we recommend detailed examinations of the vestibular system but simultaneously probing for possible co-morbidities. Since aging often entails deterioration of multimodal processes related to maintained mobility and postural stability, our results add focus on the importance of addressing balance disorders together with additional medical conditions.